Dickson Charge Pump Rectifier Using Ultra-Low Power (ULP) Diode For Ban Applications - Wong, Yan Chiew; Tan, Pei Chee; Mat Ibrahim, Masrullizam; Ahmad Radzi, Syafeeza; Abdul Hamid, Norihan (Penerbit Universiti, UTeM, 2016)
-